Rheumatologists in Ecuador: Results of a Survey - Maldonado, Genessis (Scientifica (Cairo), 2020)
INTRODUCTION: Currently, there are no records of the current status of rheumatologists in Ecuador. OBJECTIVE: The purpose of this study is to get to know the current status of rheumatologists in Ecuador, focusing on education, working conditions, productivity, distribution of time between work activities, and job satisfaction. MATERIALS AND METHODS: A digital survey was created using the Google Forms platform. It was distributed to all rheumatologist members of the Ecuadorian Society of Rheumatology. The data analysis was carried out using the statistical program SPSS v.23®. RESULTS: A total of 64 surveys were received. The response rate was 86.48%. 62.5% were men and 37.5% women, with an average age of 40.76 ± 9.18. The main workplace was state/public hospital (56.3%). The average working hours per week were 40.35 ± 25.72. Most rheumatologists in Ecuador (62.5%) received their training abroad. 79.7% of rheumatologists earn less than $ 49,000 annually. The mean retirement age was 66.51 ± 6.7, and 54.7% have a retirement plan. The average satisfaction of Ecuadorian rheumatologists was 5.4 ± 1.33 [0–7]; 17.2% are very dissatisfied with their annual income. CONCLUSIONS: This is the first recorded data on the characteristics of rheumatologists in Ecuador. Most rheumatologists obtained their specialist degree abroad. In general, rheumatologists in Ecuador are satisfied with their clinical practice and dissatisfied with their annual income and job security.